2012
DOI: 10.1016/j.ccr.2011.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenic Cells Are Common in Mouse MPNSTs but Their Frequency Depends upon Tumor Genotype and Assay Conditions

Abstract: SUMMARY Tumor-initiating cells have been suggested to be rare in many cancers. We tested this in mouse malignant peripheral nerve sheath tumors (MPNSTs) and found that 18% of primary and 49% of passaged MPNSTs cells from Nf1+/−;Ink4a/Arf−/− mice formed tumors upon transplantation whereas only 1.8% to 2.6% of MPNSTs cells from Nf1+/−;p53+/− mice did. MPNST cells of both genotypes require laminin binding to β1-integrin for clonogenic growth. Most MPNST cells from Nf1+/−;Ink4a/Arf−/− mice expressed laminin wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 51 publications
(77 reference statements)
2
21
0
Order By: Relevance
“…Survival as well as tumor incidence was compared with C57BL/6, Cpt1c gt/gt and Nf1 þ / À : p53 þ / À mice (Figure 6a). Similar to previous reports, 19,20 we observed that Nf1 þ / À : p53 þ / À mice developed soft tissue sarcomas of the limbs and abdomen as well as lymphomas at around 3-6 months of age and with a penetrance of over 70%. CPT1C depletion in this murine tumor model highly increases the median survival time from 5-15 months (Po0.0001).…”
Section: Resultssupporting
confidence: 79%
“…Survival as well as tumor incidence was compared with C57BL/6, Cpt1c gt/gt and Nf1 þ / À : p53 þ / À mice (Figure 6a). Similar to previous reports, 19,20 we observed that Nf1 þ / À : p53 þ / À mice developed soft tissue sarcomas of the limbs and abdomen as well as lymphomas at around 3-6 months of age and with a penetrance of over 70%. CPT1C depletion in this murine tumor model highly increases the median survival time from 5-15 months (Po0.0001).…”
Section: Resultssupporting
confidence: 79%
“…In benign skin tumors, addition of stromal cells-either cancer-associated fibroblasts (CAFs) or endothelial cells (ECs)-is required for tumor propagation (44). Depending on the tumor genotypes, some malignant peripheral nerve sheath tumors require the addition of laminin for successful engraftment (45). These findings indicate that transplantation assays need to be adapted and optimized for each tumor subtype, possibly by cotransplantation of different components of the tumor stroma, such as CAFs or ECs, or by the addition of exogenous components of the CSC niche.…”
Section: Cancer Stem Cells In Solid Tumorsmentioning
confidence: 99%
“…We addressed this question in mouse models of malignant peripheral nerve sheath tumors (MPNSTs) (Buchstaller et al, 2011). We found that approximately 20% of mouse MPNST cells have the potential to form tumors, even when transplanted into fully immunocompetent mice.…”
Section: Tumorigenic Cells Are Abundant In Some Cancersmentioning
confidence: 99%